2(1H)-Pyrazinones from acyclic building blocks: methods of synthesis and further derivatizations. Issue 2 (4th January 2023) - Riesco-Llach, Gerard; Planas, Marta; Feliu, Lidia; Joule, John A.
Abstract : 2(1 H )-Pyrazinones are found in natural and synthetic bioactive molecules. Methods for their synthesis by combining acyclic compounds are reviewed, from the earliest ones at the beginning of the 20th century to those described in recent years. Abstract : Pyrazinones (2(1 H )-pyrazinones) are found as components of a range of natural substances and are involved in the preparation of a great number of bioactive molecules. Synthesis of such compounds, and analogues, requires knowledge of the heterocyclic properties of pyrazinones and, in particular, methods for their ring construction. This review deals with the strategies that have been developed for the synthesis of pyrazinones from acyclic precursors, especially α-amino acid-derived units, from the first examples in 1905 up to the most recent in 2021.